Injury incidence, body site, and severity in soccer players aged 6-18 years: Implications for injury prevention - Rumpf, M. C.; Cronin, J. (Strength and Conditioning Journal, 2012)
Injury incidence data for youth participants in soccer have been collated and summarized. Such information should form a basis for injury prevention practices. Player contact accounts for most injuries (40-66%), whereas the lower extremities are considered the most vulnerable injury site in the body (70%). Strains (24%), sprains (31%), and contusions (20%) account for 75% of all injuries reported throughout the included literature. These soft tissue injuries result in minor (1-3 days, 18%), mild (3-7 days, 36%), and moderate (>1 week, 30%) recovery durations. Specific considerations for injury prevention programs are presented.